Answer
a. (f o g) (x) = x
b. (g o f) (x) = x
c. (f o g) (9) = 9
d. (g o f) (9) = 9
Step-by-step explanation
f(x) = 3x - 2
g(x) = (x + 2)/3
Note that
a) (f o g) (x) means we write f(x) and replace x with g(x)
(f o g) (x) = f[g(x)]
![\begin{gathered} =f\lbrack(x+2)/(3)\rbrack \\ =3((x+2)/(3))-2 \\ =x+2-2 \\ =x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xo768yc4nzrlpndlufjg9hbfemoqzime79.png)
b) (g o f) (x) means we write g(x) and replace x with f(x)
(g o f) (x) = g[f(x)]
= g[3x - 2]
![\begin{gathered} =(\lbrack(3x-2)+2\rbrack)/(3) \\ =(3x)/(3) \\ =x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7i7udamlj7a4bs5fhgf2g2uyqcpm1dce2q.png)
c) (f o g) (x) = x
(f o g) (9) = 9
d) (g o f) (x) = x
(g o f) (9) = 9
Hope this Helps!!!